RELATIONSHIP AND PERIODICITY OF SOLAR CORONAL HOLE AREA WITH THE SOLAR WIND SPEED AND GEOMAGNETIC ACTIVITY - Tiar Dani, M.Si (Lembaga Penerbangan dan Antariksa Nasional, 2019)
Space weather disturbances during solar minimum are more dominantly caused by the appearance of the coronal hole in the sun. In this paper, we developed tools called DeLuNa to detect and calculate the geo-effective corona hole area based on 19.3nm images from the Atmospheric Imaging Assembly instrument on Solar Dynamics Observatory (SDO/AIA193). The results from geoeffective coronal hole detection and measurement from 2016 - 2018 then used to conduct cross-correlation (cc) analysis and wavelet analysis with the solar wind speed and Dst index. We found that an increase in the area of the coronal hole will cause solar wind speed to increase at 3.17 days later (cc = 0.65). Increasing the area of the coronal hole will also cause Dst index to decrease at 3.58 days later (cc = -0.35). While the decrease in the Dst index will only take 2 hours since the increased of the solar wind speed (cc = -0.59). Wavelet analysis short-term periodicities, i.e. 27, 13.5 and 7-9 days. The observed periodicities show that changes in solar wind speed and geomagnetic storm during minimum solar activity are more dominant caused by the geoeffective coronal hole total area.